Pengembangan Media Power Point Interaktif Pada Materi Poster Kelas III SDN 190 Pekanbaru - Aisya Rahma; Febrina Dafit (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the development process, validity, and practicality ofinteractive PowerPoint media on poster material for third-grade elementary schoolstudents. The research method used was Research and Development (R&D) withthe ADDIE model. Primary data were obtained from interviews with teachers andstudents, as well as evaluations from validators, while secondary data werecollected from books and journals relevant to the study. Data collection techniquesincluded interviews and questionnaires. The research instruments consisted ofinterview sheets, validation sheets, and limited trial questionnaires. Data wereanalyzed both qualitatively and quantitatively. Qualitative analysis was based onsuggestions and comments, while quantitative analysis was obtained fromvalidation scores, teacher and student responses, and practicality scores. Thevalidation results of the interactive PowerPoint media indicated a very valid categorywithout any revision. This is reflected in the validation results, with an average scoreof 97.32% for the material aspect, 95% for the language aspect, and 97.32% for themedia aspect. The practicality test achieved an average score of 100%, showing avery positive response from teachers and students toward the interactivePowerPoint media on poster material.